(untitled) (Politeja, 2015)
This paper discusses a conceptual relationship between Europeanization and communication‑development. It analyses the theories and methods of diffusion of knowledge and information in Europeanizing and developing societies. More precisely, it focuses on the exact elements of communication‑development which coincide with Europeanization, and to what extent they could be extrapolated to the studies on internalization of the EU‑driven social change. In this regard, the article aims to identify the focal points for possible application of such a perspective and sanction further analyses of communication as a consolidating factor in the process of Europeanization.